THE RELATIONSHIP BETWEEN PARENTING STYLE AND CHILDREN LEARNING DISCIPLINE - Nurhadi Nurhadi (STAI Hubbulwathan Duri, 2020)
The purpose of this study is to determine parenting as applied by parents in Kelurahan Rawang Empat and to what extent parents' understanding of the relationship between parenting and children's learning discipline, as well as the causes of parenting. This research uses descriptive method with correlational research analysis techniques. Based on the analysis conducted showed that in the Rawang Empat sub-district Bandar Petalangan sub-district Pelalawan District parenting patterns in primary school children with an average value of 27.43 included in the category of